The system matters: corruption and vote choice in Uganda. Issue 4 (2nd October 2015) - Faller, Julie K.
Abstract : Many theories of democratic accountability expect voters to 'throw the rascals out', yet high corruption and electoral competition coexist in many African countries. Extant explanations for the persistence of corruption – including coercion, lack of information, and vote buying – are insufficient to explain these patterns. To more fully explain this, this article makes a theoretical distinction between voters' perceptions of the corruption of the political system and of individual politicians. Evidence from original interviews and focus group discussions, as well as public opinion data shows that many Ugandan citizens perceive their political system to be highly corrupt. Citizens react to these perceptions in two ways, each of which undermines electoral accountability for corrupt officials. First, many voters do not object to, and may even prefer, corrupt politicians in a system where a single 'honest' official is unlikely to reduce corruption overall. Second, some citizens respond to perceptions of system-wide corruption with disengagement, and fail to turn out to vote at all. These two trends together make it unlikely that electoral competition is sufficient to reduce corruption in Uganda.